Economic Geography Study For the Analysis of Traditional Market Distribution Patterns in East Jakarta - Umar El Izzudin Kiat; Mustikarani, Wini; Hidayat, Rahmad; Syaharu Putri Awalliyah; Sari, Yulia Puspita (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2026)
Traditional markets play an important role in supporting urban economic activities, particularly as fa-cilities for meeting daily needs and strengthening local economies. Despite the rapid growth of modern markets, traditional markets continue to exist and remain an integral part of urban economic dynam- ics. This study aimed to analyze the spatial distribution pattern of traditional markets in East Jakarta City to assess the equity of economic activities. The research employed a spatial analysis approach based on Geographic Information Systems (GIS) using the Nearest Neighbour Analysis (NNA) method. Data on traditional market locations were obtained from the Indonesian Ministry of Trade’s Satu Data Perdagangan and Google Maps, then processed using ArcGIS 10.8 software. The results showed that there were 72 traditional markets distributed across all districts in East Jakarta; however, the distribu-tion was uneven. The Nearest Neighbor Ratio (NNR) value of 0.785, with a z-score of 3.486 and a p-value of 0.000049, indicated a statistically significant clustered distribution pattern. This clustering was influenced by population density, accessibility, and historical development factors. The findings of this study provide valuable insights for regional planning and policy evaluation related to the arrange-ment of traditional markets to achieve a more equitable and efficient distribution.